Les Chypriotes, des Lusignan à l’Empire ottoman (1184-1878) : l’émergence des relations intercommunautaires gréco-turques - Mathieu Petithomme (Cahiers Balkaniques)
This article re-evaluates the evolution of Cypriots’ socio-political situation in the “long term”, by comparing the periods of domination of the Lusignan, the Venetians and the Ottomans. On the basis of historical documents and testimonies, it shows how fiscal and religious oppressions were more important during the Lusignan and Venetians dynasties as compared with the ottoman period. The ottoman conquest of Cyprus (1570-1571) implied the end of serfdom, the emergence of an autonomous education system and the development of religious freedom through the powers that were granted to the island’s archbishop. Contrary to what contemporary Greek and Turkish nationalisms pretend, justifying radicalism or separatism, this article insists on the pacifism of inter-communal relations during the ottoman period. They were founded on rural solidarities, on the respect of religious pluralism and the autonomy of each community, in a political system that combined a weak ottoman temporal power, that of the Governor, with a strong and popular spiritual power, that of the orthodox archbishop.